2020
DOI: 10.3390/ijerph17144941
|View full text |Cite
|
Sign up to set email alerts
|

Basic Psychological Needs, Burnout and Engagement in Sport: The Mediating Role of Motivation Regulation

Abstract: The purpose of the present research was to analyze the mediating role of motivational regulation between the satisfaction of basic psychological needs and burnout and engagement in athletes. From different sports 1011 young Spanish athletes participated in the study. Participants completed several measurement instruments concerning: the Basic Needs Satisfaction in Sport Scale, Behavioral Regulation in Sport Questionnaire, Athlete Burnout Questionnaire and Athlete Engagement Questionnaire. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
6
17
0
4
Order By: Relevance
“…Furthermore, in the case of our model, motivation accounted for 23% of the variance of burnout (see Figure 1 ). The results of previous research support these findings, where the same relationship was found and where motivation could explain significant proportions of the burnout variable [ 39 , 40 ]. Indeed, a review of this question led to the conclusion that burnout and its three dimensions are negatively influenced by extrinsic and intrinsic motivation and positively in the case of amotivation [ 41 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, in the case of our model, motivation accounted for 23% of the variance of burnout (see Figure 1 ). The results of previous research support these findings, where the same relationship was found and where motivation could explain significant proportions of the burnout variable [ 39 , 40 ]. Indeed, a review of this question led to the conclusion that burnout and its three dimensions are negatively influenced by extrinsic and intrinsic motivation and positively in the case of amotivation [ 41 ].…”
Section: Discussionsupporting
confidence: 79%
“…As in other recent research projects [ 38 , 39 ], a significant positive relationship was found between motivation and engagement, although the three studies used different instruments to measure the motivation variable. Specifically, the model shows that 15% of the variance of engagement can be explained through motivation, compared with 15% and 21% in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 51%
“…This finding is in accord with the results of previous studies of university students in Malaysia [ 50 ] and medical students in Korea [ 51 ]. The evidence from this study in the Thai context is similar to those of previous studies reporting that burnout is inversely related to the fulfillment of basic psychological needs and engagement [ 52 , 53 ]. These findings suggest that medical schools should design curricula that engage students and fulfill their basic psychological needs.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, the relation between regulations and engagement is of particular interest for educators, striving to improve students’ learning. Studies have consistently found a positive relationship between composite measures of autonomous motivation and engagement among students at most stages of the educational system ( Jang, 2008 ; Shih, 2008 ; Jang et al, 2016a ; Cai and Liem, 2017 ; Coelho et al, 2019 ) as well as for extracurricular activities such as sport ( De Francisco et al, 2020 ). In Shih (2008) , autonomous motivation among Grade 8 students was positively associated with behavioral engagement (involvement, persistence, and participation) and negatively associated with avoidance behaviors.…”
Section: Introductionmentioning
confidence: 99%